Venezuela's 2017 Crisis: A Failed Bolivarian Experiment or a Legitimate Claim of US Imperialism?. Issue 1 (2nd January 2018) - Antonopoulos, Paul; Cottle, Drew
Abstract : With Venezuela having the world's largest oil reserves and located within the supposed US-dominated Western Hemisphere, Venezuela's sovereignty and limited control of its own oil has threatened the control of US capitalism in the majority of Latin America. The 2017 crisis in Venezuela caused by US-backed opposition is seen in the context of the US attempting to remove a sovereign and independent government from power, resembling the Syrian crisis in 2011. This paper will analyse the context of the current crisis in Venezuela as a coordinated effort by Washington to target the Bolivarian revolution. The most critical question though is why? Washington is attempting to counter a Chinese penetration into Latin America and to stop a threat to the US dollar's domination on the region. However, despite Caracas blaming Washington for its current crisis, do the opposition have legitimate claims to the failures of the Bolivarian experiment?